Relevance of Bacteriophage 933W in the Development of Hemolytic Uremic Syndrome (HUS) - Del Cogliano, Manuel E.; Pinto, Alipio; Goldstein, Jorge; Zotta, Elsa; Ochoa, Federico; Fernández-Brando, Romina Jimena; Muniesa, Maite; Ghiringhelli, Pablo D.; Palermo, Marina S.; Bentancor, Leticia V. (Frontiers in Microbiology, 2018)
Hemolytic uremic syndrome (HUS) is associated to infections with Shiga-toxin-producing Escherichia coli (STEC). Shiga toxins (Stxs) are known as the principal responsible for HUS development. We previously report Stx2 expression by host cells in vitro and in vivo. Due to the genes encoding the two subunits of Stx are located in the genomes of bacteriophages, the aim of this study was to evaluate the role of bacteriophage induction in absence of E. coli O157:H7 genomic background. Mice were inoculated with a non-pathogenic E. coli strain carrying on the bacteriophage 933W as lysogen (C600933W) and bacteriophage excision was induced by antibiotic. Mice died after 72 hours of infection developing pathogenic damage typically observed after STEC infection. Renal and intestinal damage was observed in mice infected with C600993W. Moreover, markers of central nervous system (CNS) injury were observed, including aberrant immunolocalization of NeuN in neurons and increased expression of glial fibrillary acidic protein (GFAP). Our results showed that bacteriophage 933W without E. coli O157:H7 background is capable to reproduce pathogenic damage induced by STEC infection. Also, we developed a novel mice model to evaluate therapeutics approaches focused on the bacteriophage as a new target.